The Relationship Between the Behaviour of Pregnant Women in Recognising Pregnancy Hypertension and Preeclampsia Incidence in Medan Community Health Centre - Siti Saidah Nasution (Talenta Publisher, 2025)
Preeclampsia is a condition with increased blood pressure in pregnant women that occurs after 20 weeks of gestation. Maternal behaviour in pregnancy care is important to study to prevent the risk of preeclampsia, such as knowledge, attitudes and actions. This study aims to identify the relationship between the behaviour of pregnant women in knowing hypertension with the incidence of eclampsia in pregnant women in the working area of Puskesmas Kampung Baru Medan. A quantitative, descriptive-correlational design was employed using a cross-sectional approach. Data were analyzed using frequency distribution and percentage tables. The data in this study are presented in the form of frequency distribution tables and percentages. The findings revealed that the majority of respondents demonstrated adequate knowledge (55%), positive attitudes (62.5%), and appropriate preventive actions (82%). A moderately strong correlation was found between maternal knowledge and the incidence of preeclampsia (p = 0.00; r = 0.398). However, no significant associations were observed between attitudes (p = 0.204) or preventive actions (p = 0.117) and preeclampsia occurrence These results underscore the need to enhance maternal knowledge regarding pregnancy-related hypertension to effectively prevent preeclampsia. Keyword: Preeclampsia, Behaviour, Care, Pregnancy